Utilization of Coconut Coir Waste as an Organic Planting Medium (Cocopeat) as a Substitute for Topsoil in Crop Cultivation - Ainun Samosir; Lisa Junita; Darmiati (NASUWAKES: Jurnal Kesehatan Ilmiah, 2026)
According to the Central Statistics Agency (2021), coconut production in Aceh reaches 66.4 thousand tons, and coconut fiber accounts for approximately 12 percent of the total coconut production annually. This substantial coconut fiber potential is not fully utilized in production, leading to environmental problems. The aim of this research is to reduce coconut fiber waste by processing it into an organic planting medium (cocopeat) to replace soil. This research used an experimental method and was conducted from February 25 to April 3, 2025. The subjects used organic planting media consisting of 100% cocopeat, an 80:20 cocopeat and soil ratio, a 50:50 cocopeat and soil ratio, and 100% soil as a control. Results of water absorption tests showed that cocopeat could retain 300% of its water content, and water retention tests showed that cocopeat could retain 200% of its water content after 6 hours of sun exposure. Stem growth and leaf number of mustard greens and spinach were better in the 100% cocopeat growing medium, and observations were made weekly for 30 days. The conclusion of the test results for mustard greens and spinach plants shows that stem growth and the number of plant leaves are better at a concentration of 100% Cocopeat planting media, this proves that Cocopeat can be used as an organic planting media to replace soil.